Post-acuerdo de paz y su incidencia en la transformación urbana de Gaitania, Colombia - Laura Pinilla Loaiza; Ángel Castañeda Rodriguez (Cidades, Comunidades e Território)
The signing and implementation of the Peace Agreements between the Colombian Government and the Revolutionary Armed Forces of Colombia have generated impacts in Colombian territory. Particularly, we found significant changes in territorial ordering, demographic dimension, land use, roads and infrastructure of public services of the 16 subregions, 170 municipalities and 11,000 villages prioritized by the Development Programs with a Territorial Approach, planning, ordering and management instruments. of resources within the framework of the Comprehensive Rural Reform. The article analyzes the influence of the post-peace agreement on the physical-spatial transformations of the township of Gaitania, Colombia. It is proposed that, through the application of surveys, documentary research of primary and secondary sources and field work, it is possible to generate an analysis of a physical, social and economic nature. The results indicate a process of urban consolidation, with an increase in the mix of uses and high-rise construction, as well as improvements in infrastructure and services. Finally, the limitations related to the scarcity of data and studies in small populated centers and the importance of analyzing this type of urban phenomena in the Colombian post-conflict context are highlighted.